2009
DOI: 10.1080/08923970802629593
|View full text |Cite
|
Sign up to set email alerts
|

Glycated chitosan as a new non-toxic immunological stimulant

Abstract: Chitosan is capable to stimulate immune responses. However, because chitosan is not water soluble, it has limited biological applications. By attaching galactose molecules to the chitosan molecules, a new water-soluble compound, glycated chitosan (GC), was synthesized. GC was designed for immune stimulations in combination with phototherapies in the treatment of metastatic tumors. To investigate the possible toxicity of GC, cultures of normal and tumor cells were incubated with GC of different concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 33 publications
(36 reference statements)
0
46
0
Order By: Relevance
“…In addition, recent studies suggest that COS have potential anti-inflammatory properties in vivo and in vitro. For example, Song et al reported that COS may be a potential immunoadjuvant for the treatment of metastatic tumors [11] . In the studies…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies suggest that COS have potential anti-inflammatory properties in vivo and in vitro. For example, Song et al reported that COS may be a potential immunoadjuvant for the treatment of metastatic tumors [11] . In the studies…”
Section: Introductionmentioning
confidence: 99%
“…The pre-clinical studies showed that GC was non-toxic [10][11]. In our clinical studies, no systemic toxicity was observed following injection of GC.…”
Section: Toxicity Of Glycated Chitosanmentioning
confidence: 64%
“…The two principles underlying LIT are (1) local heating of the primary tumor with a laser (which may be combined with a light-absorbing agent to facilitate the heating) to devitalize the tumor and liberate tumor antigens, and (2) local injection of glycated chitosan (GC), a potent nontoxic immunoadjuvant that interacts with the liberated tumor antigens to induce an immune response against the cancer [10][11]. In our pre-clinical studies, we have observed the eradiation of treated primary tumors and also untreated metastatic tumors at distant sites, along with long-term, strong tumor-specific immunological responses [12][13][14][15][16].…”
Section: Laser Immunotherapymentioning
confidence: 99%
“…5 The immunoadjuvant glycated chitosan (GC) was formulated to enhance the activation of the immune system. 6 GC is biocompatible, water soluble, and capable of increasing the concentration of cytokines as well as activating immune cells. 7,8 Additionally, GC can be used as a surfactant.…”
Section: Introductionmentioning
confidence: 99%